Diabetic dyslipidaemia. Issue 4 (August 2016) - Soran, Handrean; Schofield, Jonathan D.; Adam, Safwaan; Durrington, Paul N.
Abstract : Purpose of review: The purpose is to discuss recent developments in the understanding of lipoprotein metabolism in diabetes, the cardiovascular risk associated with both type 1 and type 2 diabetes, recently published guidelines on the management of this risk, concerns over the use of statin treatment in diabetes, and other therapeutic options. Recent findings: Diabetic dyslipidaemia can be gross with massive hypertriglyceridemia, or subtle with a lipid profile which would be regarded as normal in a nondiabetic patient, but which hides underlying increases in atherogenic subfractions of LDL (e.g., small dense LDL, glycated LDL) and remnant lipoproteins. Statins can decrease these without the clinician being aware from routine biochemistry. In type 2 diabetes, HDL cholesterol levels are often reduced, whereas in type 1, insulin can raise HDL, but its antiatherogenic properties are compromised. Dyslipidaemia and hypertension predate the onset of glycaemia of diabetic proportions (metabolic syndrome). Obese people can thus die of diabetes before they develop it. Obesity should be prevented and treated. Statins decrease the risk of cardiovascular disease in diabetes or metabolic syndrome regardless of whether glycaemia worsens. Summary: One unassailable truth is that statin therapy is beneficial and should rarely, if ever, be withheld.